Evaluation of ocular surface temperature in post-COVID-19 patients with different degrees of fever via infrared thermal imaging - Chunbo Wu; Baicheng Li; Yuanshen Huang; Banglian Xu; Songlin Zhuang; Zhensheng Gu (Scientific Reports)
Abstract This study aimed to evaluate ocular surface temperature (OST) in post-COVID-19 patients with different degrees of fever via infrared thermal imaging. There were 16 participants (32 eyes) in the control group, 22 participants (44 eyes) in the moderate and low post-COVID-19 fever group (M & L fever group), and 18 participants (36 eyes) in the high post-COVID-19 fever group (H fever group). All participants underwent an ophthalmic slit lamp examination and ocular thermography. Among the control group, M & L fever group and H fever group, there were no significant differences in the upper eyelid temperature (UET), inner canthus temperature (ICT), outer canthus temperature (OCT), initial central corneal temperature (initial CCT), third-second central corneal temperature (3s-CCT), or sixth-second central corneal temperature (6s-CCT). However, the change in central corneal temperature measured within 1, 3, and 6 s (change in CCT within 1, 3, and 6 s) of the H fever group were significantly greater than those of the control group (0.15 ± 0.12 °C vs. 0.08 ± 0.09 °C, p = 0.007; 0.30 ± 0.22 °C vs. 0.17 ± 0.17 °C, p = 0.005; 0.45 ± 0.30 °C vs. 0.26 ± 0.23 °C, p = 0.004, respectively) and M & L fever group (0.15 ± 0.12 °C vs. 0.08 ± 0.08 °C, p = 0.008; 0.30 ± 0.22 °C vs. 0.16 ± 0.14 °C, p = 0.001; 0.45 ± 0.30 °C vs. 0.23 ± 0.20 °C, p < 0.001, respectively). To further investigate the relationship between OST and post-COVID-19 fever, we compared the OST of long recovery time (5 days < recovery time < 14 days; 9 patients, 18 eyes) and short recovery time (recovery time ≤ 5 days; 9 patients, 18 eyes) in the H fever group. We found that the 6s-CCT in the short recovery time group was significantly lower than that in the long recovery time group (32.43 ± 1.09 °C vs.33.10 ± 0.82 °C, p = 0.044). Additionally, the change in CCT within 1 s, 3 s, and 6 s in the short recovery time group were all significantly greater than those in the long recovery time group (0.19 ± 0.13 °C vs. 0.11 ± 0.10 °C, p = 0.048; 0.38 ± 0.24 °C vs. 0.22 ± 0.17 °C, p = 0.026; 0.58 ± 0.31 °C vs. 0.32 ± 0.24 °C, p = 0.016, respectively). In conclusion, the central corneal temperature (CCT) of patients who have an insufficient recovery time from COVID-19 infection or who exhibit severe infection symptoms could decrease faster when the eyes open. This may be due to dry eye disease.